2018
DOI: 10.1037/hea0000571
|View full text |Cite
|
Sign up to set email alerts
|

Psychological symptoms and subsequent healthy lifestyle after a colorectal cancer diagnosis.

Abstract: Among women with CRC, higher anxiety and depression symptoms were associated with subsequent unhealthier lifestyle in the 10 years following diagnosis. With replication, such findings may suggest that treating psychological symptoms early in the cancer trajectory may not solely reduce psychological distress but also promote healthier lifestyle. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 69 publications
3
23
0
Order By: Relevance
“…Previous research on psychological health and lifestyle behavior among CRC survivors has shown an association between higher psychological distress and an unhealthier lifestyle [6,31,32]. Trudel-Fitzgerald et al [31] found that among women with CRC from the Nurses' Health Study prospective cohort in the USA, higher levels of anxiety and depression symptoms were associated with subsequent unhealthier lifestyle in the 10 years following CRC diagnosis [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research on psychological health and lifestyle behavior among CRC survivors has shown an association between higher psychological distress and an unhealthier lifestyle [6,31,32]. Trudel-Fitzgerald et al [31] found that among women with CRC from the Nurses' Health Study prospective cohort in the USA, higher levels of anxiety and depression symptoms were associated with subsequent unhealthier lifestyle in the 10 years following CRC diagnosis [31].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on psychological health and lifestyle behavior among CRC survivors has shown an association between higher psychological distress and an unhealthier lifestyle [6,31,32]. Trudel-Fitzgerald et al [31] found that among women with CRC from the Nurses' Health Study prospective cohort in the USA, higher levels of anxiety and depression symptoms were associated with subsequent unhealthier lifestyle in the 10 years following CRC diagnosis [31]. Although, to our knowledge, no other study has specifically assessed the association between psychological distress and diet quality among CRC survivors, two studies have assessed the association between psychological distress and physical (in)activity in CRC survivors [6,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various mechanisms may explain the observed distress-mortality association. A less healthy lifestyle, as defined by engaging in fewer healthy behaviors and having an unhealthy BMI, is related to having more distress symptoms [ 45 ] and with reduced subsequent overall and cancer-specific survival [ 46 ] among CRC patients. In our study, accounting for lifestyle at baseline and 4 years later did not alter the relationship of anxiety or depression with mortality, suggesting behavioral factors are not a primary pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In this pooled sample of two Dutch CRC survivor cohorts, we observed that alcohol consumption is slightly decreasing after Over time, we found that survivors who were male, with higher education, more physical activity, and survivors without a stoma reported higher consumption of alcoholic drinks. At baseline, we found that our study population had more alcohol consumers than reported in other cancer survivor studies: 49% current consumers [14], 8% moderate consumers [24], and 88% low alcohol consumption (≤ 1 drink/day) [25], but all alcoholic consumptions seemed to decrease slightly in the 2 years post-diagnosis. This was in line with the paper of Bours et al stating that 95% drank less alcohol after CRC diagnosis in a cross-sectional study 7 years post-diagnosis [26].…”
Section: Discussionmentioning
confidence: 44%